ANALYSIS OF BANK SHARIA INDONESIA'S FINANCIAL PERFORMANCE BEFORE AND AFTER THE MERGER - Kosim, Nanang; Wardana, Ditya (I-Finance Journal, 2024)
The aim of this research is to find out whether there are changes in the financial performance of Bank Syariah Indonesia before and after the merger. The population and sample used were 3 sharia banks that merged into PT. Bank Syariah Indonesia (BSI) which includes PT. Bank Syariah Mandiri (BSM), PT BNI Syariah (BNIS), and PT BRI Syariah (BRIS). Observation data is in the form of quantitative information taken from annual financial reports for the pre-merger period 2019-2020 and the post-merger period 2021-2022. The research methodology used includes descriptive statistics using the maqashid sharia index (MSI) technique. The findings of the data analysis show that financial performance as measured by MSI for the ranking results, BNIS is ranked first, BSI is second, BRIS is third and BSM is fourth. BNIS received first place with superior results for the first and second performance indicators, while BRIS's third indicator was superior. Even though BNIS was ranked first in the MSI results, the average MSI results before the merger from the combination of BRIS, BNIS and BSM were still lower than the MSI results of BSI bank. The conclusion shows that the financial performance using the BSI bank MSI technique is better after the merger if compared to before the merger based on the average of pre- and post-merger MSI results..